2005
DOI: 10.1111/j.1460-9592.2005.01517.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial comparing overnight preoperative fasting period Vs oral administration of apple juice at 06:00–06:30 am in pediatric orthopedic surgical patients

Abstract: A 15 ml.kg(-1) of apple juice for patients of <3 years of age or 10 ml.kg(-1) for older children, at 06:00-06:30 am of the surgical morning is a simple procedure to prevent dehydration and to produce positive behavior in low-risk, pediatric surgical patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 11 publications
1
49
0
5
Order By: Relevance
“…Moreover, it possibly causes disturbances in the fluid balance, which is a poor base for induction, and may even slow down recovery [37]. On the other hand, several studies have shown shorter fasting guidelines to be safe and beneficial [38,31,15,32]. Changes in the practice have been delayed mainly because of fear of aspiration of the gastric contents [31].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, it possibly causes disturbances in the fluid balance, which is a poor base for induction, and may even slow down recovery [37]. On the other hand, several studies have shown shorter fasting guidelines to be safe and beneficial [38,31,15,32]. Changes in the practice have been delayed mainly because of fear of aspiration of the gastric contents [31].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the practice have been delayed mainly because of fear of aspiration of the gastric contents [31]. When employing new fasting guidelines, neither aspiration nor other complications related to the fasting time have increased, and the patients have been more satisfied [38,32]. Previous research has shown that children undergoing tonsillectomy/adenotonsillectomy suffer from significant postoperative pain, nausea and vomiting [1,4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7][8] Óþarflega löng fasta hefur margvísleg neikvaeð áhrif á líkamsstarfsemi og líðan skurðsjúklinga, og eru þorsti, höfuðverkur, hungurtilfinning, þreyta, kvíðatilfinning, sljóleiki og svimi þekkt einkenni. 4,9,10 Löng fasta veldur einnig þurrki, insúlínónaemi, vöðva-rýrnun og veikir ónaemissvörun. 4,11 Rannsóknir sýna að neysla kolvetnaríkra drykkja tveimur til þremur klukkustundum fyrir aðgerð sé örugg, hún minnki Inngangur: Fasta sjúklinga er mikilvaeg öryggisráðstöfun fyrir skurðað-gerð.…”
Section: Inngangurunclassified